Factors influencing visitors' evaluation of service quality in Giant Panda Conservation Centre (GPCC), Zoo Negara - Yee, Lai Ling (2016)
Giant Panda Conservation Centre (GPCC) is dedicatedly established with RM 25 million to house the giant pandas which were loaned from China to commemorate the 40 years diplomatic ties between China and Malaysia. However, service quality of GPCC is yet to be determined even though the centre has received many visitors since its establishment in the year 2014. In addition, GPCC management has no directions to enhance its service quality. Therefore, service quality study should be conducted to determine the visitors’ satisfaction towards the service quality and as well to find out the factors which influence it. SERVPERF model was adopted in this study by using four points Likert Scale as the measurement. The study is targeted at school holidays’ visitors who are varied in socio-demographic characteristics. By using the Statistical Package for the Social Sciences (SPSS), descriptive analysis and regression analysis have been carried out. The findings show that generally, visitors were satisfied with the service quality of GPCC. Among all the seven attributes, education / learning attribute was most satisfied whereas the consumable attribute was least satisfied from the perception of visitors. However, visitors were dissatisfied with the item “reasonable price of food and drink sold”. Furthermore, visitors’ re-visit intention, visitors’ recommendation intention, religion, age, and sources of information were the factors that influence the satisfaction level of visitors. In short, subsequent and effective steps should be taken by the management to enhance the service quality in GPCC.